Informe De Pasantía En La Dian – División De Fiscalización Y Liquidación Cambiaria (2024)
The DIAN plays a key role in the administration and collection of taxes, as well as in the facilitation of international trade through customs management, tax and exchange rate. It is also responsible for ensuring the implementation of special projects and some priority processes within the entity, through organizational units that they work not only at the central level, but also at the local level to achieve their implementation